Selçuk Type Headgear-Tımer" (Stht) (Clınıcal Evaluatıon And Its Affects On Patıent Co-Operatıon) Part Iı: Clınıcal Study - Enis Güray; Metin Orhan (Galenos Yayinevi, 1994)
In the present study, the clinical evaluation of previously described (Part I) "STHT" was carried out. Its effect on patient co-operation was also investigated. In the first part, JO patients were intsructed to use their headgear's for 16 hours a day. Following the 2 month treatment period, the timer devices on headgears were introduced to the patients and a second 2 month examination period was initiated. At the end of the second period the headgear wear time was increased 26%. In conclusion, "STHT" with its substantial contribution on patient co-operation and wear-resistant qualities may be considered as a safe approach to extraoral therapy. And also, timer's must he used at the reseacrhes related to the effects of headgears.